Development of a novel device for measurement of pedal force in cycling - Fuglsang, T.; Kersting, U. G. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
A device was developed to be mounted between a cycling shoe and cleat with the ability to measure force perpendicular to the pedal. The device consists of a PolyPower force sensor placed in between two aluminium plates connected by three bolts. Furthermore, a mechanism allowing pulling forces to be measured is explained. The device was comparable to a golden standard when pushed upon, but did not provide valid measurements of pulling forces. In order to function as a valid and reliable power meter or a device capable of measuring pedal forces, the sensor´s recovery rate should be improved along with the pulling mechanism of the device while angular sensors could be added for assessment of pedal kinematics.